Konseling Islam Untuk Mengatasi Masalah Psikologi Remaja Dampak Perceraian Orang Tua (Studi Kasus Pada Klien “H” Di Desa Pulau Harapan) - Nurkholis Abdillah; Kusnadi; Mana Rasmanah (CV. ITTC INDONESIA, 2024)
This research is entitled Islamic Counseling to Overcome Adolescent Psychological Problems Impact of Parental Divorce (Case Study of Client